2008
DOI: 10.1002/anie.200801325
|View full text |Cite
|
Sign up to set email alerts
|

NO Dismutase Activity of Seven‐Coordinate Manganese(II) Pentaazamacrocyclic Complexes

Abstract: Redox selectivity? Seven‐coordinate manganese(II) pentaazamacrocyclic complexes stimulate NO disproportionation by a novel dismutation mechanism based on the formation of labile metal–nitrosyl adducts and which is associated with the MnII/MnIII redox cycle. The metal‐bound NO in these aducts has the character and reactivity of NO− and NO+ species. Ex vivo studies suggest that superoxide dismutase mimics of this kind could interfere with NO‐mediated processes in biological milieu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…This response was also independent of the GC-cGMP-PKG axis but reversed by application of reducing agents, suggesting that NO had a direct effect on ASIC probably through oxidation of cysteine residues. With respect to the GC and cGMP-independent pronociceptive actions of NO donors, one must consider that the mitochondrial superoxide dismutase also acts as NO dismutase producing the highly reactive nitroxyl anion (NO Ϫ ) which nitrosylates thiol groups in proteins (e.g., critical cysteines in TRPA1) creating posttranslational modifications of potentially sustained functional effect (197).…”
Section: Mechanisms Of Peripheral Pronociceptive Actions Of Nitric Oxidementioning
confidence: 99%
“…This response was also independent of the GC-cGMP-PKG axis but reversed by application of reducing agents, suggesting that NO had a direct effect on ASIC probably through oxidation of cysteine residues. With respect to the GC and cGMP-independent pronociceptive actions of NO donors, one must consider that the mitochondrial superoxide dismutase also acts as NO dismutase producing the highly reactive nitroxyl anion (NO Ϫ ) which nitrosylates thiol groups in proteins (e.g., critical cysteines in TRPA1) creating posttranslational modifications of potentially sustained functional effect (197).…”
Section: Mechanisms Of Peripheral Pronociceptive Actions Of Nitric Oxidementioning
confidence: 99%
“…or 4?) cations that stem from their potential applications as molecular magnets [1][2][3], in biochemistry [4,5] and homogeneous catalysis [6,7] due to its intriguing inherent nature and various oxidation states including 2?, 3?, 4?, 6? to 7?.…”
Section: Inroductionmentioning
confidence: 99%
“…This way, the role of NO is preserved, and subsequent formation of peroxynitrite is prevented (which can additionally be removed by porphyrintype of SOD mimics) (3,19,68). Because of this main dogma, only few studies tested a direct reaction of the SOD mimics with NO (20,21,56,63). Since our previous findings showed that manganese-SOD could react with NO through a dismutation mechanism (23), we studied in detail the reaction of penta-azamacrocyclic SOD mimics with NO in vitro (20) and on cellular models (21).…”
mentioning
confidence: 99%
“…Because of this main dogma, only few studies tested a direct reaction of the SOD mimics with NO (20,21,56,63). Since our previous findings showed that manganese-SOD could react with NO through a dismutation mechanism (23), we studied in detail the reaction of penta-azamacrocyclic SOD mimics with NO in vitro (20) and on cellular models (21). We observed that these complexes catalyze NO dismutation, that is, generation of reactive nitrosonium (NO + ) and nitroxyl (NO -/HNO) species; the former being able to cause S-nitrosylation of protein thiols and the latter their oxidation (66).…”
mentioning
confidence: 99%